Penerapan Pembelajaran STEAM Berbasis Games Logix Untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik di SMP Negeri 8 Ambon - Carolina Sri Athena Barus; Sally Untajana; Fryan Sopacua; Venty Sopacua; Jhony Taihuttu; Yansen Kapitan (Postgraduate, University of Mataram, 2026)
This study aims to describe the application of STEAM learning based on Logix games to improve students' critical thinking skills in science (Physics) material at SMP Negeri 8 Ambon. This study uses quantitative and qualitative research methods, a quasi-experimental type of research involving an experimental group and a control group. The sampling method is carried out randomly. The sample in this study consisted of 46 students. The design used was a pre-test post-test control group design. The research design was Quasi-Experimental. Data analysis in this study was conducted using quantitative descriptive analysis to describe the data as it is in the form of percentages and explain the data or events with explanatory sentences qualitatively and also used differential statistical analysis. The data analysis techniques used include: independent t-test and N-Gain test for test results and qualitative descriptive response test. The results of the N-Gain test found that in the control class using the conventional model, most students did not experience an increase in critical thinking skills with a percentage increase in the low category of 82.35% and a medium category of 17.65%, while for the experimental class it was found that the experimental class using the STEAM approach based on games logic on critical thinking skills experienced an increase in cognitive critical thinking skills with a percentage in the high category of 13.04%, medium of 78.26%, and low of 8.7%, this is supported by the value of the independent t-test with a 2-tailed sign value of less than 0.05 at the assumed equal variances value, there is a significant difference between the control and experimental classes where the treatment of the experimental class affects the student's grades, causing the grades to be higher than the value of the control class that was not given any treatment, so in general it can be concluded that the application of the STEAM approach based on games logic in science learning provides significant opportunities for students to develop critical thinking skills.